New distribution record of the Greater False Vampire Bat (Megaderma lyra, Geoffroy 1810) from North-Western Himalaya: Distribution of Megaderma lyra in Garhwal Himalaya - Devendra Singh; Dinesh Kumar Sharma (Journal of Tropical Life Science, 2023)
India has been stated to have 10% of the world's total bat's diversity. The present survey was aimed to study the bat species diversity, distribution and activity patterns in north-western Himalayan region of India. Field surveys were conducted and echolocation calls were recorded using bat detector, Echometer touch 2 in Shiwalik ranges of Himalaya. The Greater False Vampire Bat (Megaderma lyra) has a broad distribution range that stretches from south to south east Asia. In India the distribution of the species was mostly recorded from southern subtropical coastal regions and north-eastern subtropical moist evergreen forests. In the present study The Greater False Vampire Bat (Megaderma lyra) has been recorded for the first time from Garhwal region of north-western Himalayas. Greater False Vampire Bat (Megaderma lyra) having long forearm (>6.63 ± 0.03cm) and lengthy ear (>3.66 ± 0.08cm), which is a distinguishable feature of the family Megadermatidae. The peak frequency (FMaxE) of echolocation was recorded as 50.295 ± 9.18 kHz. This frequency was initiated at 108.20 ± 2.51 kHz and terminated at 30.76 ± 1.37 kHz. The call structure recorded was very distinguishable and specific to this family.